Synchronous and asynchronous HEVC parallel encoder versions based on a GOP approach. (November 2016) - Migallón, H.; Hernández-Losada, J.L.; Cebrián-Márquez, G.; Piñol, P.; Martínez, J.L.; López-Granado, O.; Malumbres, M.P.
Abstract: In this paper, we focus on applying parallel processing techniques to HEVC encoder in order to significantly reduce the computational power requirements without disturbing its coding efficiency. So, we propose several, synchronous and asynchronous, parallelization approaches working at a coarse grain parallelization level, based on the Group Of Pictures (GOP), which we call GOP-based level. GOP-based approaches encode simultaneously several groups of consecutive frames. Depending on how these GOPs are conformed and distributed it is critical to obtain good parallel performance . The results show that near ideal efficiencies are obtained using up to 10 cores. Furthermore, when the computational load is unbalanced, the asynchronous versions outperform the synchronous ones. The parallel algorithms developed in this work support all standard coding modes proposed by the reference software.